FUNDAMENTALS OF THE DESIGN OF MEDICAL INSTITUTIONS - Qodirova Surayyo Odilovna; Axmedov Shuhrat Umarovich (Scholar Express Journals, 2022)
In this article, the typology of medical buildings, general rules of building design, methodical-plan Solutions, General Plan of buildings, auxiliary building and design systems of rooms are described. Issues of construction of medical buildings are covered. When designing medical buildings, it is necessary to take into account the traditions and climatic conditions of the local population in accordance with the requirements of the current period, to formulate and develop the architecture of buildings that have all the amenities and are suitable for the world classrooms
Keywords: Innovative; Composition; Structure; Optimal